Maxillary sinus unplugged: dealing with foreign bodies in the maxillary sinus - Mahesh, Lanka; Juneja, Saurabh; Rajagopal, Athreya; Dhawan, Zara (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Foreign bodies lodged within the maxillary sinus are rare occurrences, presenting diagnostic challenges and requiring tailored surgical interventions. We report a case of male in his mid-sixties, with a history of chronic sinusitis complaining of broke teeth and asking for replacement or the same. Imaging revealed an ectopic tooth lodged within the right maxillary sinus. Infected Schneiderian membrane was intentionally removed and foreign body was removed from the sinus employing innovative techniques to safely remove the foreign body and a long-standing collagen membrane was used to recreate the sinus floor. Postoperatively, the patient experienced complete resolution of symptoms and restoration of sinus function. This case emphasizes the importance of thorough preoperative evaluation and how dental professionals can effectively manage unique cases in their clinical practice with optimal patient outcome in managing maxillary sinus foreign bodies.